META-ANALISIS PENGARUH METODE OUTDOOR LEARNING TERHADAP HASIL BELAJAR IPA - Amaludin, La; Pelenusa, Rahim; Awal, Rawia (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Background: This study aims to determine the effect of outdoor learning methods on science learning outcomes. Outdoor Learning is a form of teaching where in the learning process the teacher uses outdoor learning as a medium so that students can know something real and can think critically and objectively. Methods: This study uses a meta-analysis method. Meta Analysis is research that discusses similar articles. The data collection technique is to collect articles related to the influence of outdoor learning methods on science learning outcomes. The sample used in this study were 15 related articles. Data collection techniques by giving Pretest and Posttest. Data analysis uses the effect size calculation technique using the Glass formula. Results: The results showed that there was a significant effect of the outdoor learning method on biology learning outcomes with an average effect size of 0.637. Conclusion: The outdoor learning method has an effect on biology learning outcomes. The use of outdoor learning methods has an effect on biology learning outcomes, this is in accordance with the results of calculations with an average effect size value of 0.637. Outdoor learning involves many senses so that it can provide a memorable experience because students can absorb more material.